2004
DOI: 10.1002/cncr.20758
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of BCR‐ABL induces apoptosis in imatinib mesylate‐resistant cell lines

Abstract: BACKGROUNDImatinib mesylate, a BCR‐ABL tyrosine kinase inhibitor, induces apoptosis in chronic myeloid leukemia cells. Resistance to imatinib is currently the most important concern of this treatment. One of the main mechanisms of this resistance is overexpression of BCR‐ABL.METHODSIn the current study, the authors investigated the correlation between BCR‐ABL overexpression and apoptosis in BaF/BCR‐ABL and LAMA84 cell lines resistant to imatinib suddenly deprived of the inhibitor, and compared with their sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
2
11
0
1
Order By: Relevance
“…This also explains the attenuated cell growth and increased apoptosis rate of KCL22-R after Imatinib withdrawal. Similar results were reported for the cell lines BaF/BCR-ABL and LAMA84 where withdrawal of Imatinib induced apoptosis (34).…”
Section: Discussionsupporting
confidence: 77%
“…This also explains the attenuated cell growth and increased apoptosis rate of KCL22-R after Imatinib withdrawal. Similar results were reported for the cell lines BaF/BCR-ABL and LAMA84 where withdrawal of Imatinib induced apoptosis (34).…”
Section: Discussionsupporting
confidence: 77%
“…We found that the removal of dasatinib induces apoptosis after 6 hours. It has been reported that the removal of imatinib leads to the apoptosis of BCR/ABL-overexpressing leukemic cells via a transient activation of the STAT5/Bcl-xL pathway (34). In this study, the BCR/ABL protein was reduced in dasatinib-resistant cells, suggesting that another mechanism was involved in the apoptotic process.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, activation of the PDGF receptor results in apoptosis in cultured vascular smooth muscle cells in a time-and dose-dependent manner, involving decreased levels of Bcl-2 and Bcl-xL mRNA (Okura et al 1998). Overexpression of tyrosine kinases might be associated with a decrease in cell proliferation, as exemplified by upregulation of the Bcr-Abl protein due to amplification of the BCR-ABL gene in human imatinib-resistant cell lines (Desplat et al 2005).…”
Section: Discussionmentioning
confidence: 99%